To rewrite the equation \((4x/(3x - 12)) + 3 = 10\) in two equations joined by "and", we can isolate the fraction on one side. Here's how we can do it:
-
Start with the original equation: \[ \frac{4x}{3x - 12} + 3 = 10 \]
-
Subtract 3 from both sides: \[ \frac{4x}{3x - 12} = 7 \]
Now we can write this as two equations:
- \(\frac{4x}{3x - 12} = 7\)
- \(\text{and}\) \(3x - 12 \neq 0\) (to avoid division by zero)
So the final result is: \[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 3x - 12 \neq 0 \]